Betydningen af professionernes værdiskabelse for forskning og udvikling - Lindeberg, Tobias Høygaard (Tidsskrift for Professionsstudier, 2018)
The purpose of this article is to strengthen the impact of research and development at university colleges by offering models for professional value creation. The legal framework of the university colleges strongly emphasized that research and development must contribute to the value creation of the professionals. Three distinct models are offered as a mean to qualify the research and development activities: A model of professional value creation as a system, a production factor model and evidence-based practice as a model for value creation.